Effect of trailing edge serration-flow misalignment on airfoil noise emissions. (29th September 2017) - Arce León, Carlos; Merino-Martínez, Roberto; Ragni, Daniele; Avallone, Francesco; Scarano, Fulvio; Pröbsting, Stefan; Snellen, Mirjam; Simons, Dick G.; Madsen, Jesper
Abstract: The broadband noise generated by the scattering of turbulent flow at the trailing edge of a NACA 0018 airfoil with trailing edge serrations is investigated, varying both the airfoil angle of attack and serration flap angle. Acoustic emissions from the trailing edge are measured using a microphone array. The noise level is observed to be higher than that of the airfoil without serrations at frequencies beyond a crossover value. The latter is found to scale with a characteristic Strouhal number based upon the boundary layer thickness and the freestream velocity. A satisfactory collapse of the results under varying angles of attack and freestream velocities is observed. The modifications of the hydrodynamic behavior and the noise increase are linked by high-speed observations conducted with particle image velocimetry. An increase in the energy of turbulent fluctuations is also observed at the expected crossover frequency. The dominant cause of the increased noise is thereby identified at the pressure side edge of the serrations at a given flap angle.